The effect of atmospheric elements in the upper atmosphere on the emergence and development of thunderstorms in Medina | أثر العناصر الجوية في طبقات الجو العليا في نشأة العواصف الرعدية وتطورها في المدينة المنورة - Al Khateeb | الخطيب, Hamid Musa | حامد موسى (Al-Madinah Al-Munawwarah Research and Studies Center | مركز بحوث ودراسات المدينة المنورة, 2023)
Research topic: pp. 7 - 58 | موضع البحث: ص 7 - 58